Applying Knowledge of Species‐Typical Scavenging Behavior to the Search and Recovery of Mammalian Skeletal Remains. Issue 2 (9th November 2015) - Young, Alexandria; Stillman, Richard; Smith, Martin J.; Korstjens, Amanda H.
Abstract: Forensic investigations involving animal scavenging of human remains require a physical search of the scene and surrounding areas. However, there is currently no standard procedure in the U.K. for physical searches of scavenged human remains. The Winthrop and grid search methods used by police specialist searchers for scavenged remains were examined through the use of mock red fox ( Vulpes vulpes ) scatter scenes. Forty‐two police specialist searchers from two different regions within the U.K. were divided between those briefed and not briefed with fox‐typical scavenging information. Briefing searchers with scavenging information significantly affected the recovery of scattered bones (χ 2 = 11.45, df = 1, p = 0.001). Searchers briefed with scavenging information were 2.05 times more likely to recover bones. Adaptions to search methods used by searchers were evident on a regional level, such that searchers more accustom to a peri‐urban to rural region recovered a higher percentage of scattered bones (58.33%, n = 84).